Application of the Hungarian Assignment Method to Minimize Normal Cases in Cinderella Tempe Chips MSMEs - Pesta Gultom; Ester Sabrina Aruan; Ribka Callista Simangunsong; Viona Anggraini br Ketaren; Winda Rosianna Tampubolon (Outline Journal of Management and Accounting, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the national economy, including the Cinderella Tempeh Chips MSME. To address efficiency and productivity challenges, an appropriate management approach is needed, one of which is the Hungarian minimization method for production assignment. This research explores the application of the Hungarian method to solve minimization assignment problems at the "Cinderella" Tempeh Chips MSME. By transforming production activity data, such as processing, frying, and packaging, into a cost/time matrix, this method aims to minimize the total operational time or cost. The main stages involve row and column reduction to create zero elements, covering zeros with the minimum number of lines, and matrix adjustments until an optimal solution is found. Previous studies in MSMEs, service industries, and warehousing have shown that this method provides significant optimal solutions. The results obtained can help MSMEs improve production efficiency and market competitiveness.